Socioeconomic status and university students’ perceptions of English as a professional language - Barrios-Espinosa, María Elvira; López-Agudo, Luis Alejandro (My University, 2021)
The study behind this paper aimed to assess the influence of the socioeconomic status (SES) on university students’ expectations of English use in their prospective career and their perceptions of English competence as a key professional skill. The sample consisted of 109 students from two Bachelor Degree courses at the University of Málaga (Spain), one in Energy Engineering and the other one in Pedagogy. An ANOVA analysis revealed that there was no statistically significant difference between the three SES groups in the sample as to their expectations and perceptions concerning English competence. However, descriptive statistics show that the participants in the lower SES group have lower expectations regarding the role of English in their future career. Additionally, the students in this group hold a lower perception of English as a key professional skill. These findings lead us to conclude that lower SES students may be less inclined to enroll in partially or fully taught English courses at university, and that their perceptions may actually be a factor in their future career prospects in areas where English is extensively used as a lingua franca.
Keywords: Universitarios - Situación económica; Inglés - Enseñanza; English Medium of Instruction (EMI); Higher Education; Student' perceptions; Socioeconomic status (SES)